The new role of university teachers, century XXI - Salazar Savinovich, Franklin (Revista Universidad de Guayaquil, 2012)
The phenomenon of globalization is a multidimensional process that encompasses many aspects such as economics, finance, science, technology, communication, education, politics, among others; however, economic globalization is the guiding force behind all the others.